ENVIRONMENTAL ASSESSMENT OF MICROBASINS OF RIBEIRAO BONITO AND RIBEIRAO CUIABA, IN PONTAL DO PARANAPANEMA/SP: ANALYSIS OF CHARACTERISTICS OF FOREST FRAGMENTS REMAINING - Santori, Alisson Rodrigues; Gouveia, Jose Mariano Caccia [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2020)
The development of this study was oriented on the possibility of contribute to the evaluation and the conditioning of environmental characteristics of specific clippings of the Brazilian geographic space, in this sense, the proposed work provides conditions to evaluate and reflect on the environmental issues and concerns in Pontal do Paranapanema region. The implementation of this study has organized and produced information and data on the environmental characteristics of the remaining vegetation of two micro-basins located in the municipalities of Teodoro Sampaio and Mirante do Paranapanema in the state of Sao Paulo. The main objective of this work is not limited only to produce a report or generally characterizing the physical surroundings and environmental conditions, but also to collaborate both theoretically and technically on the possibility of environmental recovery and restoration of the most interesting within the observed cutout. The results obtained were achieved by building a methodology that would compile, in an organized way, several pieces of preliminary information and database supporting the steps of environmental analysis of the area at the office and in the fieldwork, and also a later thematic mapping of the area with different geoprocessing techniques. The theoretical understanding of this work has been founded on the appropriation of the idea that the activities implemented within the micro-basin has direct and indirect effects on the characteristics and, consequently, the environmental quality of the area; and whereas certain uses have produced harmful suppressions, impacts and shifts to the environment.
Keywords: Geoprocessing; Land Uses; NDVI; Conservation Unit